Modelling Seabed Ploughing Using the Material Point Method. (2017) - Cortis, Michael; Coombs, William M.; Augarde, Charles E.; Robinson, Scott; Brown, Michael; Brennan, Andrew
Abstract: Ploughing of the seabed is needed for the installation of cables and pipelines and is an area of construction likely to increase given plans in the UK and elsewhere for offshore marine energy (wind and tidal). Seabed ploughing is an expensive and sometimes risky operation for which there are limited guidelines as to what the tow force and speed is for an expected trenching profile within a specified ground condition. Most ploughing schemes are designed using semi-empirical approaches, with very few computational tools able to take into account the geometric and material nonlinearity inherited by the ploughing problem. In this paper we describe how the Material Point Method (MPM) is being used as a numerical tool to model seabed ploughing with the aim of providing an improved predictive tool for the future, via an EPSRC-funded research project at Durham and Dundee Universities. Various issues are discussed in the paper including the means of modelling moving essential boundaries and the choice of basis functions, and this new method in MPM is demonstrated on a simple ploughing problem.